Flipped Learning in Fostering Students' Independent Learning through Self-Regulation and Parental Supervision (Flipped Learning dalam Menumbuhkan Kemandirian Belajar Siswa melalui Regulasi Diri dan Pengawasan Orang Tua) - Muhajir Muhajir; Syahrul Syahrul (Shautut Tarbiyah, 2022)
This article aims to provide an analysis of flipped learning in fostering student learning independence through self-regulation and parental supervision. The aspects studied are: flipped learning in fostering student learning independence through self-regulation and flipped learning in fostering student learning independence through parental supervision. The method used in this article is a literature review, where readings are carried out on various scientific journals that discuss flipped learning. The results of the study show that the application of flipped learning can lead students to achieve independent learning, but must be supported by high self-regulation and optimization of parental supervision. Independent learning of students is not only influenced by the involvement of parents and students' personal factors, but also includes environmental factors. This study suggests the need for collaboration between teachers and parents in formulating a supervisory model for students and training students' self-regulation.Keywords:     Flipped Learning, Learning Independence, Self Regulation, Parental Supervision, Digital Age Artikel ini bertujuan memberikan analisis tentang flipped learning dalam menumbuhkan kemandirian belajar siswa melalui regulasi diri dan pengawasan orang tua. Aspek yang didalami adalah: flliped learning dalam menumbuhkan kemandirian belajar siswa melalui regulasi diri dan flliped learning dalam menumbuhkan kemandirian belajar siswa melalui pengawasan orang tua. Metode yang digunakan dalam artikel ini adalah reviu literature, dimana pembacaan dilakukan terhadap berbagai jurnal ilmiah yang membahasa tentang flipped learning. Hasil kajian menunjukkan bahwa penerapan flipped learning dapat mengantar siswa mencapai kemandirian belajar, tetapi harus ditunjang dengan regulasi diri yang tinggi dan optimalisasi pengawasan orang tua. Kemandirian belajar siswa tidak hanya dipengaruhi oleh keterlibatan orang tua dan faktor pribadi siswa, tetapi juga mencakup faktor lingkungan. Kajian ini menyarankan perlunya kolaborasi guru dan orang tua dalam merumuskan model pengawasan bagi siswa dan melatih regulasi diri siswa.Kata Kunci:   Flliped Learning, Kemandirian Belajar, Regulasi Diri, Pengawasan Orang Tua, Era Digital